2020
DOI: 10.7717/peerj.9381
|View full text |Cite
|
Sign up to set email alerts
|

The validity of activity trackers is affected by walking speed: the criterion validity of Garmin Vivosmart® HR and StepWatch 3 for measuring steps at various walking speeds under controlled conditions

Abstract: Introduction The use of activity trackers has increased both among private consumers and in healthcare. It is therefore relevant to consider whether a consumer-graded activity tracker is comparable to or may substitute a research-graded activity tracker, which could further increase the use of activity trackers in healthcare and rehabilitation. Such use will require knowledge of their accuracy as the clinical implications may be significant. Studies have indicated that activity trackers are not sufficiently ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
(121 reference statements)
1
17
0
Order By: Relevance
“…Fokkema et al after testing 10 different step counting devices came to a similar conclusion as the above mentioned team: the activity trackers performed better at an average and vigorous walking speed than at a slower walking speed [ 15]. Several other publication confirm their findings [16][17][18]. Tedesco et al made a significant remark that even though the activity trackers were quite accurate in counting steps but underestimated calories so clinicians should be cautious in considering other parameters provided by these devices for clinical or research purposes [18].…”
Section: Discussionsupporting
confidence: 54%
“…Fokkema et al after testing 10 different step counting devices came to a similar conclusion as the above mentioned team: the activity trackers performed better at an average and vigorous walking speed than at a slower walking speed [ 15]. Several other publication confirm their findings [16][17][18]. Tedesco et al made a significant remark that even though the activity trackers were quite accurate in counting steps but underestimated calories so clinicians should be cautious in considering other parameters provided by these devices for clinical or research purposes [18].…”
Section: Discussionsupporting
confidence: 54%
“…Prior to assessment, participants were fitted with two AG’s and one Stepwatch (SW) activity monitor. SW has been shown to be sensitive to detect steps over a range of gait speeds, especially during slow walking [ 21 ]. The position of the accelerometers was guided by Webber and St. John [ 8 ] with the AG accelerometers attached around the right hip (above the iliac crest) and left ankle (proximal to the lateral malleolus), and the SW reference sensor positioned on the right ankle (proximal to the lateral malleolus) [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…The hip is the most commonly used placement for measuring walking since the hip accurately reflects the center of mass of the body. However, since slow walking generally has low acceleration amplitudes and the amplitude decreases from the ground upwards, the signal measured at the hip might not be sufficient Sensors 2021, 21, 3154 2 of 10 to cross the proprietary threshold for detecting a step. Previous studies have shown AG to accurately detect steps at a gait speed of >1.0 m/s [5,10], whereas few studies have investigated the sensitivity of AG to detects steps at different ranges of gait speeds < 1.0 m/s.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the unquestionable usefulness of these metrics from a health point of view, there are some concerns about the validity and quality of the information provided by accelerometers, namely for other populations rather than healthy adults in which most of these metrics we validated, such as the elderly [ 13 ]. Researchers have shown that WDs have low accuracy to assess the number of steps performed at low velocities such as those below 2 km·h −1 [ 14 , 15 ]. Although this may not be a serious issue in adults or healthy elderly with no mobility limitations, the opposite can be quite true for subjects with substantial gait pattern changes prompted by neurological impairments or other orthopedic or musculoskeletal limitations, such as the elderly, who are frequently cane and walker-users [ 16 ].…”
Section: Monitoring Physical Activity and Energy Expenditure—accelerometer Wearable Devicesmentioning
confidence: 99%